Chronic Infection Contributes to the Risk of Limb Amputation in Patients with Diabetic Ulcers: A Literature Review - Wenny Anugraini; Fitri Arofiati; Yanuar Primanda (Indonesian Journal of Global Health Research, 2026)
Diabetic foot ulcers are a chronic complication of diabetes mellitus that often leads to lower extremity amputation and significantly contributes to disability and mortality. Infections, particularly chronic and severe ones, play a significant role in accelerating ulcer progression to amputation, Nevertheless, the synthesis of scientific evidence regarding the contribution of chronic infections as a determinant of amputation is still limited. This literature review aimed to examine the role of chronic infection in the risk of amputation in patients with diabetic foot ulcers. A literature search was conducted on the Scopus, PubMed, and ScienceDirect databases for publications from 2015 to 2025 using keywords related to diabetes mellitus, diabetic foot ulcers, infection, and amputation. Articles were selected based on inclusion and exclusion criteria, 644 articles were identified. After title and abstract screening, followed by full-text review, and critical appraisal using the JBI tools, 10 selected journals were included in the literature synthesis.. The results indicated that moderate to severe infection, osteomyelitis, and pathogen characteristics, particularly Gram-negative and ESBL-producing bacteria, are the main determinants of major amputation. Peripheral artery disease, the severity of ulcers, increased inflammatory parameters, hypoalbuminemia, and certain patient factors also worsen clinical outcomes. It is concluded that chronic infection is a key determinant of amputation in diabetic foot ulcers, making early and aggressive infection prevention and control an essential strategy to reduce amputation rates.